PENGARUH SUPLEMENTASI TEPUNG KROKOT (Portulaca oleraceae l) DENGAN TARAF YANG BERBEDA TERHADAP KADAR TOTAL PROTEIN PLASMA, ALBUMIN DAN GLOBULIN KAMBING JAWARANDU (Capra aegagrus hircus) - Andi Setiawan; Siswanto Siswanto; Erwanto Erwanto; Muhtarudin Muhtarudin (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to determine the best dose of purslane flour on total plasma protein, albumin, and globulin in Jawarandu Goats. This research was conducted in February-March 2021 at the Rambon Asri Farmer Group, Rejo Asri Village, Seputih Raman District, Central Lampung Regency, Lampung Province. Examination of total plasma protein, albumin, and globulin was carried out at the Veterinary Center of Lampung Province. The experimental design used was a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments were basal ration (P0), basal ration with 5% purslane flour supplementation (P1), basal ration with 10% purslane flour supplementation (P2), and basal ration with 15% purslane flour supplementation (P3). The data obtained were analyzed using analysis of variance with a significance level of 5%. The results showed that purslane flour supplementation had no significant effect (P>0.05) on total plasma protein, albumin, and blood globulin of Jawarandu Goats but remained in the normal range. Keywords : Albumi, Globulin, Jawarandu goat, Purslane flour, Total plasma protein